2020
DOI: 10.1097/md.0000000000022954
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different forms of Guizhi Fuling Wan on reproduction and metabolism in women with polycystic ovary syndrome

Abstract: Background: Polycystic ovary syndrome (PCOS), is a common endocrine disorder in women characterized by increased androgen levels, ovulatory dysfunction, and polycystic ovaries. Western medicine is widely used for the treatment of PCOS, but patient satisfaction is low, largely due to its associated gastrointestinal symptoms of nausea and diarrhea. Guizhi Fuling Wan (GFW) is a traditional Chinese medicine used to remove blood stasis and dissipate phlegm for treating gynecological diseases that was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…[4,16] Modern pharmacological studies have demonstrated that GFP exhibits significant anti-inflammatory, anticancer, anticoagulant, neuroregulatory, metabolic regulatory, and immunomodulatory effects. [16,20,21] In this study, utilizing network pharmacology and constructing a network of Chinese herbal compound regulation, we identified 6 key component nodes with the closest associations to cardiovascular diseases among the top 10 active components ranked by degree. These components, ranked in descending order of degree value, include quercetin, beta-sitosterol, baicalein, kaempferol, cerevisterol, and albiflorin, suggesting their potential crucial roles in the treatment of CSA.…”
Section: Discussionmentioning
confidence: 99%
“…[4,16] Modern pharmacological studies have demonstrated that GFP exhibits significant anti-inflammatory, anticancer, anticoagulant, neuroregulatory, metabolic regulatory, and immunomodulatory effects. [16,20,21] In this study, utilizing network pharmacology and constructing a network of Chinese herbal compound regulation, we identified 6 key component nodes with the closest associations to cardiovascular diseases among the top 10 active components ranked by degree. These components, ranked in descending order of degree value, include quercetin, beta-sitosterol, baicalein, kaempferol, cerevisterol, and albiflorin, suggesting their potential crucial roles in the treatment of CSA.…”
Section: Discussionmentioning
confidence: 99%
“…The main research methods are integrated traditional Chinese and western medicine, and the treatment methods are based on activating blood circulation and benefiting water, clearing away heat and phlegm, invigorating spleen and supplementing qi, and warming yang and benefiting water [14][15][16]; Oral administration of traditional Chinese medicine is based on Wuling San, Zhenwu Decoction, and Mufangji Decoction [17][18][19]; Chinese patent medicines are mainly injected with Xinmailong injection, ligustrazine injection and Tanreqing injection [20,21]; External treatment of TCM mainly includes acupoint application therapy, foot bath of traditional Chinese medicine, acupuncture, and auricular point pressing pills [22,23]. At present, there are few studies on the mechanism of action in this field and animal experiments are lacking, and research can be strengthened in this area in the future.…”
Section: Discussmentioning
confidence: 99%
“…7 In addition, long-term medication might cause many potential inconveniences and adverse events to the patients. [11][12][13][14][15] Serving as a type of non-pharmacological interventions, lifestyle interventions (ie, exercise, dieting) are mainly suitable for obese or overweight patients with PCOS. In order to promote fertility, invasive therapies, such as laparoscopic ovarian drilling and in vitro fertilisation-embryo transfer are only used following the non-responsiveness of pharmacological interventions, because they are invasive procedures that cause damages to the patient's body.…”
Section: Open Accessmentioning
confidence: 99%